Dakwah Kontemporer dan Radikalisme Agama di Bulukumba - Mahmuddin Mahmuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
The article aims to understand the application of contemporary dakwah in Bulukumba as an effort to tackle religious radicalism. This highlighted from a characteristic contemporary priests, contemporary dakwah materials and media of contemporary dakwah and the role of dakwah in counteracting religious radicalism in Bulukumba district of South Sulawesi. The result of this research shows that in general dai (priests) including contemporary dai. At this point, it can be said that one of the characters contemporary dakwah is contemporary priests themselves. The priests, mostly still focused on the traditional ways in presenting Islam when they give presentations. Meanwhile, matters such as contemporary medium had not been fully employed well. Ultimately, the priests play important roles in order to counter and prevent religious radicalism, and they have the role to explain proportional religious thoughts.